A Sensing Platform Using Ag/Pt Core‐shell Nanostructures Supported on Multiwalled Carbon Nanotubes to Detect Hydroxyurea. Issue 10 (9th July 2020) - Haghshenas, Mahnoosh; Mazloum‐Ardakani, Mohammad; Alizadeh, Zahra; Vajhadin, Fereshteh; Naeimi, Hossein
Abstract: Developing anticancer sensing platforms has a significant impact on individual cancer treatment. Monitoring of anticancer drugs in bodily fluid allows doctors to prescript the efficient amount of drugs that significantly lower chemotherapy side effects on individuals. In this study, for the first time, we explored a chemically modified carbon paste electrode (CPE), containing 2, 2′‐(1, 6‐hexanediylbisnitrilo‐ethylidine)‐bis‐hydroquinone (HEH) and Ag@Pt/multiwalled carbon nanotubes (MWCNTs), to monitor hydroxyurea (HU), a highly toxic anticancer drug, in human serum. The electrochemical study was carried out to determine the electrocatalytic rate constant, the diffusion coefficient, and the electron‐transfer coefficient of HU oxidation. The DPV of HU showed three linear dynamic ranges in the concentration ranges of 0.05 to 1.0 μM, 1.0 to 50.0, and 50.0 to 1000.0 μM. The detection limit was lowered to 23.0 nM. With this sensing platform, DPV peaks of mixed HU and uric acid (UA) could be isolated from each other, indicating satisfied selectivity. The proposed electrochemical sensor serves as a handy device for monitoring of HU in clinical samples. Abstract :